2021
DOI: 10.3390/admsci11030078
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Conceptual Structure of the Research on Innovation in Hotels through Co-Word Analysis

Abstract: This paper presents the results of a bibliometric analysis of published academic research on innovation in hotels. In particular, it aims to analyze the conceptual structure of the field, covering the period until October 2020, and predict emerging trends. This approach provides an exhaustive analysis of 334 papers collected from the Scopus database. Co-word analysis used to identify the conceptual structure reveals four clusters: (1) technological innovation, (2) innovativeness and innovation strategy, (3) kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…In the first step, we defined the main purpose of the study, that is, identified both the predominant themes and future research opportunities on DE and sustainability. Accordingly, in the second step, we decided to analyze the productivity of journals and authors, the impact of publications, and use as a bibliometric method the co-word analysis, which is interpreted as a representation of the conceptual structure of the research field (Donthu et al 2021;Fernandes and Pires 2021;Zupic and Čater 2015). Co-word analysis uses an advanced content analysis technique to investigate the relationships between terms/words in a set of documents (Callon et al 1983) and to delimit the boundaries of scientific areas (Castriotta et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first step, we defined the main purpose of the study, that is, identified both the predominant themes and future research opportunities on DE and sustainability. Accordingly, in the second step, we decided to analyze the productivity of journals and authors, the impact of publications, and use as a bibliometric method the co-word analysis, which is interpreted as a representation of the conceptual structure of the research field (Donthu et al 2021;Fernandes and Pires 2021;Zupic and Čater 2015). Co-word analysis uses an advanced content analysis technique to investigate the relationships between terms/words in a set of documents (Callon et al 1983) and to delimit the boundaries of scientific areas (Castriotta et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The bibliographic data were collected from Elsevier's Scopus database, which is widely used in systematic literature reviews and bibliometric analyses (e.g., Anand et al 2021;Niñerola et al 2019;Fernandes and Pires 2021). Moreover, Scopus database has a larger publications coverage in this field of research than Web of Science database (e.g., Mongeon and Paul-Hus 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Studies that investigate absorptive capacity and innovation in SMEs in the tourism sector are still very scarce. If we consider the hotel sector, the scarcity of research on innovation remains high (Fernandes & Pires, 2021). However, although it is not specifically about the hotel sector, we believe that the work of Bezerra et al (2016) The concept of knowledge absorption capacity (AC) has been defined as an organization's ability to absorb new knowledge from its environment to become more innovative and flexible, thus achieving a more favorable performance in terms of business survival (Cassol et al, 2019;Flatten et al, 2011;Lane et al, 2006).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…The literature on innovation in tourism has emphasized the need for increased empiricism and theorization on the various aspects that influence this phenomenon (Fernandes & Pires, 2021;Tejada et al, 2013;Thomas & Wood, 2015). One of these aspects is Absorptive Capacity (AC).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many global economies are moving from product-oriented to service-oriented industries (Chen et al, 2016). Consequently, service sectors are projected to become more competitive as more entrants battle to sustain a competitive advantage, and it is in this struggle that innovation capability is recognized as a critical source and force (Fernandes and Pires, 2021; Pascual-Fernández et al, 2021). Especially in developing economies, service innovation capability is seen as critical to overcoming sluggish economic growth (Rubalcaba et al, 2016).…”
Section: Introductionmentioning
confidence: 99%